New perspectives on women entrepreneurs - Butler, John E., 1946- (Emerald Publishing Limited : Information Age Pub., 2003)
This volume presents papers offering perspectives on the theme of women entrepreneurs. It is part of a series focusing on research in entrepreneurship and management.
Keywords: Businesswomen.; Women executives.; Women-owned business enterprises.; Entrepreneurship.; Feminist economics.; Business & Economics -- Women in Business.; Subject matter intended specifically for women and/or girls.; Business and Management.; Gender studies: women and girls.; elektronické knihy; electronic books